Neural correlates of implicit object identification. - Pins, D; Meyer, M; Foucher, J; Humphreys, G; Boucart, M (2004)
The present study sought to assess neural correlates of implicit identification of objects by means of fMRI, using tasks that require matching of the physical properties of objects. Behavioural data suggests that there is automatic access to object identity when observers attend to a physical property of the form of an object (e.g. the object's orientation) and no evidence for semantic processing when subjects attend to colour. We evaluated whether, in addition to neural areas associated with decisions to specific perceptual properties, areas associated with access to semantic information were activated when tasks demanded processing of the global configuration of pictures. We used two perceptual matching tasks based on the global orientation or on the colour of line drawings. Our results confirmed behavioural data. Activations in the inferior occipital cortex, fusiform and inferior temporal gyri in both tasks (orientation and colour) account for perceptual and structural processing involved in each task. In contrast, activations in the posterior and medial parts of the fusiform gyrus, shown to be involved in explicit semantic judgements, were more pronounced in the orientation-matching task, suggesting that semantic information from the pictures is processed in an implicit way even when not required by the task. Thus, this study suggests that cortical regions usually involved in explicit semantic processing are also activated when implicit processing of objects occurs.